Impact of adding nano-selenium on the quality of diluted buck semen preserved by cooling during summer and winter - Abd El-Rheem, Samia M.; El Bawab, Iman E.; Metwally, Kamal K.; El-Hadary, Ahmed E. (Journal of Advanced Veterinary Research, 2024)
Bucks reproductive performance can be improved by artificial insemination technique, that affected by many factors the most important one is semen quality, which is affected by the methods of semen preservation cooling and freezing. The goal of this study was to assess the effect of adding different concentrations of antioxidant as Nano-selenium to the diluted buck semen during preservation by cooling in both summer and winter seasons. Eight mature healthy Zaraibi bucks were used in the study. Semen samples were collected by an electro- ejaculator twice per week during summer 2021 (August, September) and winter (January, February). Samples were pooled and diluted by extender then divided to experimental groups: Group 1: Nano-selenium: 100 Î¼L / 100 ml and Group 2: 200 Î¼L / 100 ml. Â Then the groups cooled for measuring some semen parameters and seminal antioxidant activities after 1 h from adding and at 8 hours then every 8 hrs up to 64 hr. Nano selenium 200 Î¼L / 100 ml has a favorable impact on diluted buck semen during cooling preservation during summer and winter.